Exploring the Trend of Behavioral Studies in Waqf Literature A Bibliometric Analysis - Mohammad Zen Nasrudin Fajri (Universitas Darussalam Gontor, 2024)
This study aims to reveal the evolution of behavioral research in waqf literature, most influential authors, institutions and countries. It also explores the research trends and future research directions. This study analyzed 105 papers from Scopus using bibliometric approach and content analysis. The results show that behavioral analysis in waqf literature has grown steadily since 1999, with a marked rise in research output after 2017, peaking in 2024. Early studies focused on traditional waqf mechanisms, but recent research incorporates digital waqf technologies like blockchain and crowdfunding, emphasizing trust, religiosity, and attitudes as key determinants. These developments highlight the increasing integration of behavioral insights with waqf practices, reflecting broader trends in Islamic finance and socio-economic development. The field is dominated by Malaysian institutions, with Universiti Sains Islam Malaysia leading contributions, followed by Universiti Malaysia Kelantan and Universitas Airlangga. Southeast Asia, particularly Malaysia and Indonesia, plays a pivotal role in advancing waqf research. Leading authors, including Ismail S, Ratnasari RT, and Shukor SA, have significantly shaped the discourse. Major publication outlets, such as the Journal of Islamic Marketing and the ISRA International Journal of Islamic Finance, underline the regional focus on Islamic social finance. Research trends emphasize digital waqf technologies, cash waqf, and behavioral determinants like trust and attitudes. Future studies could explore generational differences, innovative waqf models, and the impact of digitalization on participation. Addressing these areas could enhance waqf’s socio-economic impact and broaden its appeal to diverse stakeholders globally